Immune response treated with bone marrow mesenchymal stromal cells after stroke - Wang, Zili; Wang, Xudong; Liao, Yidong; Chen, Guangtang; Xu, Kaya (Frontiers in Neurology, 2022)
Stroke is a leading cause of death and long-term disability worldwide. Tissue plasminogen activator (tPA) is an effective treatment for ischemic stroke. However, only a small part of patients could benefit from it. Therefore, finding a new treatment is necessary. Bone marrow mesenchymal stromal cells (BMSCs) provide a novel strategy for stroke patients. Now, many patients take stem cells to treat stroke. However, the researches of the precise inflammatory mechanism of cell replacement treatment are still rare. In this review, we summarize the immune response of BMSCs treated to stroke and may provide a new perspective for stem cell therapy.